2014
DOI: 10.1111/cei.12341
|View full text |Cite
|
Sign up to set email alerts
|

Ductal epithelial expression of Ro52 correlates with inflammation in salivary glands of patients with primary Sjögren's syndrome

Abstract: SummaryRo52 is an E3 ubiquitin ligase with a prominent regulatory role in inflammation. The protein is a common target of circulating autoantibodies in rheumatic autoimmune diseases, particularly Sjögren's syndrome (SS). In this study we aimed to investigate the expression of the SS target autoantigen Ro52 in salivary glands of patients with primary Sjögren's syndrome (pSS). Ro52 expression was assessed by immunohistochemical staining of paraffinembedded and frozen salivary gland biopsies from 28 pSS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…Similar increased expression of Ro-52 has been reported in salivary ductal epithelium as well, and the level of expression tallied with the degree of inflammation [59]. Further evidence for Ro-52 in autoimmunity comes from two Ro-52 deficient mice models [54,60].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar increased expression of Ro-52 has been reported in salivary ductal epithelium as well, and the level of expression tallied with the degree of inflammation [59]. Further evidence for Ro-52 in autoimmunity comes from two Ro-52 deficient mice models [54,60].…”
Section: Introductionsupporting
confidence: 57%
“…Increased Ro and La expression has been demonstrated in MSG of patients with SS as compared with controls [59,66]. Also those with higher La expression were detected to have higher anti-La antibody implicating antigen driven autoantibody response [67].…”
Section: Introductionmentioning
confidence: 99%
“…26 27 Inflammatory conditions in SG of patients with pSS have been shown to induce ductal expression of Ro52. 28 In addition, expression and location of Ro52 in different cellular compartments have been modulated by activation of innate immunity through toll-like receptor 3 (TLR3), interferon-alpha (IFN-α) and nitric oxide. [29][30][31] In NZM2758 mice, we observed that alum treatment caused significant upregulation of circulating KC, IL-1α, MIG, MIP2 and PDGF-β (see online supplementary figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests Ro52+ (not only the antibody) may have an important role in autoimmunity 34 35. The expression of Ro52 protein correlates with inflammation in autoimmune diseases, for example, salivary glands in primary SS 36. Although these antibodies have been reported in many autoimmune diseases,37 they are not specific given that they have been detected in other systemic conditions without autoimmune features 27 38 39.…”
Section: Introductionmentioning
confidence: 99%